Pavlovian to instrumental transfer responses do not correlate with addiction-like behavior in rats - Takahashi, Tatiane T.; Vengeliene, Valentina; Enkel, Thomas; Reithofer, Sara; Spanagel, Rainer (Frontiers in behavioral neuroscience, 2019)
Pavlovian learning plays a prominent role in the etiology of addiction. The influence of Pavlovian conditioning on the expression of an instrumental response can be studied using the Pavlovian-to-instrumental transfer (PIT) paradigm. This paradigm consists of independent Pavlovian conditioning and instrumental training prior to the combination of both during the test. During this test the reward is not available, and an increase in the instrumental responding during conditioned stimuli presentation is a measure of PIT. Recent studies have reported a higher PIT in alcohol and nicotine dependent patients, suggesting that enhanced PIT might be a marker for dependence vulnerability. However, these studies did not use standard PIT procedures, and a clear correlation between an enhanced PIT and drug-related and addictive behaviors has so far not been demonstrated. For a systematic evaluation rats were trained in a cocaine addiction model. Addicted-like and non-addicted-like rats were subsequently assessed in the PIT paradigm. In a further experiment, rats were first tested in the PIT paradigm and thereafter subjected to cocaine self-administration training. Our results revealed that addicted-like rats did not differ from non-addicted-like in their performance in the PIT test. However, cocaine self-administration behavior showed a positive correlation with PIT. This data suggests that stronger PIT may predict higher motivational impact of conditioned stimuli on drug self-administration and improved learning of drug-cue association rather than the risk to develop addiction as such.
Gesehen am 23.10.2019